Are ultrasonographic findings like periosteal and tendinous edema associated with medial tibial stress syndrome? A case-control study. Issue 2 (February 2017) - Winters, Marinus; Bon, Paulien; Bijvoet, Sascha; Bakker, Eric W.P.; Moen, Maarten H.
Abstract: Objectives: Medial tibial stress syndrome (MTSS) is one of the most common sporting injuries. As of yet, the development of effective therapeutic interventions to treat MTSS is hindered by the fact that its pathology is unknown. Our aim was to explore the pathology of MTSS, by assessing whether the presence of MTSS is related to periosteal, bony or tendinous abnormalities in the lower leg. Design: Case-control study. Methods: Participants with MTSS and athletic control participants were recruited from the same (high-risk) base population. Musculoskeletal ultrasonography was performed on the posteromedial tibial border and deep plantar flexor muscles by an experienced radiological specialist who was blinded to group membership. Associations between MTSS and tissue abnormalities were expressed in odds ratios (OR). Results: A total of 42 participants, 15 MTSS cases and 27 control athletes completed the study. Overall, periosteal and tendinous abnormalities were common in cases with and without MTSS. Periosteal edema was present in 8 (53.3%) MTSS cases and in 10 (37.0%) control athletes, in specific painful spots in the distal 2/3 of the posteromedial tibial border OR = 1.9 (95% CI 0.54–6.99, p  = 0.35). Also, tendinous abnormalities in the tibialis posterior muscle were frequently seen in MTSS cases ( N  = 7, 46.7%) and in control athletes ( N  = 13, 48.1%) (OR = 0.97, 95% CI 0.27–3.51, p  = 0.96). No bone abnormalities were observed in either group. Conclusions: Periosteal and tendinous findings seem to be common in both athletes with and without MTSS, and consequently are not associated with MTSS.